Inflammatory Characteristics of Stenotic Aortic Valves: A Comparison between Rheumatic and Nonrheumatic Aortic Stenosis - Lars Wallby; Thora Steffensen; Lena Jonasson; Mats Broqvist (Cardiology Research and Practice)
Background. Although our comprehension of nonrheumatic aortic stenosis (NRAS) has increased substantially during the last decade, less is known about the histopathology of rheumatic aortic stenosis (RAS). The aim of this study was to investigate rheumatic aortic stenosis by means of analyses previously used in nonrheumatic stenosis. Material and Methods. Valve specimens were obtained from 39 patients referred to hospital due to significant aortic stenosis. According to established macroscopic criteria the valves were divided into two groups consisting of 29 NRAS and 10 RAS valves. Mononuclear inflammatory cells and apolipoproteins were investigated using immunohistochemical analyses. Results. The localisation of calcification differed in tricuspid nonrheumatic valves when compared to bicuspid nonrheumatic and rheumatic valves. The RAS valves revealed a lower degree of T lymphocyte infiltration compared with the NRAS valves. Infiltration of macrophages was seen in all valves and there were no differences regarding deposition of apolipoprotein. Conclusion. Rheumatic and nonrheumatic aortic stenotic valves show a similar and significant chronic inflammation. The similarities regarding the localisation of calcification indicate that the valve anomaly/morphology can influence the pathogenesis of aortic stenosis. Finally, our findings highlight the question of a postinflammatory valvular disease of other causes than rheumatic fever.